(untitled) (XXI Century. Spanish Literature and Culture, 2012)
This article intends to review the ways in which Javier Marias’s writing separates Mañana en la batalla piensa en mí from the usual realistic patterns. The relationships between actions and thinking in the protagonist, and other characters in the novel, do not help the reader in the acquisition of some knowledge or wisdom, and therefore our interpretation is always provisional, or manifestly inadequate and incomplete. From a methodological point of view I follow the narratological analysis, as was defined by Gerard Genette theories, and I try to develop a close reading paying special attention to the relationship between fiction and reality, that in this book stems from the title and a clear and repetitive allusion to Shakespeare work.